2018
DOI: 10.1002/pat.4449
|View full text |Cite
|
Sign up to set email alerts
|

Hydrophilic modification of polyvinylidene fluoride membrane by blending amphiphilic copolymer via thermally induced phase separation

Abstract: A new amphiphilic copolymer TD‐A is melt‐blended with polyvinylidene fluoride to fabricate hollow fiber membranes in order to improve the hydrophilicity and anti‐fouling property. Membrane samples with different blending ratios are prepared via thermally induced phase separation method. An optimum blending ratio of TD‐A (10 wt%) is determined by a series of characterizations to evaluate the effects of TD‐A contents on membrane properties. The hydrophilicity of the blended membrane samples increases with the in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(12 citation statements)
references
References 35 publications
0
12
0
Order By: Relevance
“…Therefore modication is necessary. Among the modication methods, polymer blending is the most common and simple method to improve the hydrophilicity of the membrane, [14][15][16] in which the compatibility between the polymers is an important factor affecting the structure and properties of the blend membranes, poor compatibility between polymers would lead to not only uneven membrane surface, but also the membrane with stripes and macroporous structure as result of poor membrane properties. 17 Therefore, suitable hydrophilic substances are prerequisite for hydrophilic modi-cation, many hydrophilic substances are blended into the PES membrane to improve the hydrophilicity of PES membrane, such as: hydroxyapatite nanotubes, 18 oxygen-doped graphitic carbon nitride, 19 CuO, 20 cellulose acetate 21 and so on.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore modication is necessary. Among the modication methods, polymer blending is the most common and simple method to improve the hydrophilicity of the membrane, [14][15][16] in which the compatibility between the polymers is an important factor affecting the structure and properties of the blend membranes, poor compatibility between polymers would lead to not only uneven membrane surface, but also the membrane with stripes and macroporous structure as result of poor membrane properties. 17 Therefore, suitable hydrophilic substances are prerequisite for hydrophilic modi-cation, many hydrophilic substances are blended into the PES membrane to improve the hydrophilicity of PES membrane, such as: hydroxyapatite nanotubes, 18 oxygen-doped graphitic carbon nitride, 19 CuO, 20 cellulose acetate 21 and so on.…”
Section: Introductionmentioning
confidence: 99%
“…To diminish the membrane-foulant hydrophobic interaction, hydrophilic modification has been implemented on the membrane substrate material via blending (Guo et al, 2019;Tao et al, 2019) or copolymerization (Sun et al, 2013;Wang S. et al, 2018), the membrane outer surface via hydrophilic (Higuchi et al, 2002;Li et al, 2015) or superhydrophilic grafting/coating (Liang et al, 2014(Liang et al, , 2018Li et al, 2018;Zhao et al, 2018;, and the inner pore walls (Liang et al, 2012). The membrane-foulant electrostatic repulsion could be enhanced or electrostatic attraction reduced by modifying the membrane charge properties via, for instance, in situ deposition of electrically conductive polymers such as polyaniline, polypyrrole, and polythiophene on the surface or in the pore structure (Zhan et al, 2004;Qiang et al, 2011;Liu et al, 2012;Sun et al, 2018).…”
Section: Membrane Modification For Tuning the Membrane-foulant Interamentioning
confidence: 99%
“…Zhao et al reported an amphiphilic copolymer poly­(2-hydroxyethyl methacrylate)-poly­(2-perfluorooctylethyl methacrylate) with surface compositional heterogeneities on the molecular scale and found that when the percentage of the fluorinated part ranged from 4 to 14% on the surface, the copolymer possessed better protein-resistance capacities than the corresponding homopolymer. Until now, various works have been done to study the effect of the balance between hydrophilicity and hydrophobicity in amphiphilic copolymers on their antiprotein adsorption performances. Among these, hard monomers containing low-surface-energy fluorinated groups (such as −CF 2 , −CF 3 ) are widely used as hydrophobic components, and a representative example is a fluoroacrylate monomer. These low-surface-energy hydrophobic components can be enriched on the surface after high-temperature annealing treatment. , However, when exposed to a water environment, these hard fluorinated components tend to be buried in the bulk and the hydrophilic components tend to migrate to the surface, which causes the antiprotein adsorption ability to be mainly dominated by the hydrophilic components rather than the synergistic effect, thus weakening the antiprotein adsorption performances.…”
Section: Introductionmentioning
confidence: 99%